Effect of aluminum on the FeCr(Al) alloy oxidation resistance in steam environment at low temperature (400 °C) and high temperature (1200 °C). (December 2022) - Chikhalikar, Atharva; Roy, Indranil; Abouelella, Hamdy; Umretiya, Rajnikant; Hoffman, Andrew; Larsen, Mike; Rebak, Raul B.
Abstract: The effect of aluminum in the FeCr(Al) alloys on the corrosion behavior was studied at two temperatures (400 °C and 1200 °C). For the Fe-21Cr alloy, Cr2 O3 layer was formed upon exposure to both temperatures. The addition of Al altered the corrosion mechanism of the alloy. At 1200 °C, a thin α -Al2 O3 is formed on the Fe-21Cr-5.5Al alloy. Whereas, at low temperature, a continuous Cr2 O3 is formed at the top with an internal Al2 O3 layer. These results show that FeCrAl alloys hold promise as Fuel Cladding Materials with Al playing a crucial role under operational as well as accident-like conditions. Highlights: Effect of Al on steam corrosion of FeCr(Al) alloys was studied at 2 temperatures. At 1200 °C, thick Cr2 O3 oxide layer formed on the Fe21Cr alloy Whereas thin Al2 O3 layer formed on the Fe21Cr5.5Al alloy At 400 °C, Fe21Cr5.5Al formed Cr2 O3 on the surface with an internal Al2 O3 layer. Presence of Al improves the corrosion resistance as compared to the Fe21Cr alloy.